(untitled) (JS (JURNAL SEKOLAH), 2021)
Abstract: Application Of Picture And Picture Learning Models To Improve Civics Learning Outcomes In Class V.A Students Of SD Negeri 256 Palembang. This study used a research action of 2 cycles and before the cycle was carried out pre-cycle data was taken. Each round consists of four stages, namely: design, activity and observation, reflection and revision. This research is based on the problem: How is the application of the Picture and Picture learning model to improve Civics learning outcomes in class V.A SD Negeri 256 Palembang students ?. From the analysis, it was found that the learning outcomes of students had increased from cycle I to cycle II. This can be seen from the more stable students’ understanding of the material presented by the teacher (learning completeness increased from the first and second cycles), namely, respectively, 53.13%, 96.88%. Keywords: Learning Outcomes, Social Studies, Picture And Picture Abstrak: Penerapan Model Pembelajaran Picture And Picture Untuk Meningkatkan Hasil Belajar Pkn Pada Peserta Didik Kelas V.A SD Negeri 256 Palembang. Penelitian ini menggunakan tindakan penelitian sebanyak 2 siklus dan sebelum siklus dilakukan telah diambil data pra siklus. Setiap putaran terdiri dari empat tahap yaitu: rancangan, kegiatan dan pengamatan, refleksi dan revisi. Penelitian ini berdasarkan permasalahan: Bagaimana penerapan model pembelajaran Picture And Picture untuk meningkatkan hasil belajar PKn pada peserta didik kelas V.A SD Negeri 256 Palembang?. Dari hasil analisis didapatkan bahwa hasil belajar peserta didik mengalami peningkatan dari siklus I sampai siklus II. Hal ini dapat dilihat dari semakin mantapnya pemahaman peserta didik terhadap materi yang disampaikan guru (ketuntasan belajar meningkat dari sklus I, dan II) yaitu masing-masing, 53.13%, 96.88%. Kata Kunci: Hasil Belajar,IPS, Picture And Picture